Conservation of a Wooden Tomb-Marker from the Jewish Cemetery of Algarrobos in Argentina - Alfieri, Paula Vanesa (2018)
The state of conservation of some tombs in the Jewish Cemetery of Algarrobos in ColoniaMauricio, Buenos Aires, Argentina was evaluated. A lot of material was found, but only twotomb-markers were done on wood. They were in a state of serious deterioration, so these were definedas an object of study. The tomb-markers, which had been established by the Jewish immigrants fromRussia at the end 19th century, were made of South American tree known as Aspidosperma QuebrachoBlanco and suffered both biological (from fungal decay and insect attack) and mechanical deterioration(cracks and fissures due to weathering, and discoloration due to ultraviolet radiation). Thus, the aimof this paper was the conservation of one of the two remaining wooden tomb-markers found,using impregnant based on non-toxic siloxanes employing sol-gel technology in order to increasethe readability of epitaphs and reliefs found at the tomb-marker. The treatment with this moderntechnology resulted in the excellent performance of wooden tomb-maker conservation. The structuralconsolidation and cracks sealing were achieved. It avoided the detachment of material and theappearance of natural veins; furthermore, it improved the reading of the epitaphs and reliefs.